Duration of Preoperative Anti-Tuberculosis Treatment (OAT) and Clinical Outcomes Post-Surgery in Spinal TB Patients: A Systematic Review and Meta-Analysis - Gusnur Gazali Ashari; Benny; Iman Dwi Winanto (Universitas Muhammadiyah Palu, 2025)
Spinal tuberculosis (TB) is a rare but severe infection that can lead to deformities, back pain, and neurological deficits. Preoperative administration of anti-tuberculosis drugs (OAT) is commonly used to reduce bacterial activity and inflammation before surgery. However, the optimal duration of OAT preoperatively is still debated. This study aims to systematically review and analyze the relationship between preoperative OAT duration and clinical outcomes post-surgery in patients with spinal TB. A systematic review and meta-analysis were performed on studies comparing the effects of different OAT durations preoperatively in spinal TB patients. Data were collected from PubMed, Scopus, and EMBASE. Key outcomes evaluated included Visual Analog Scale (VAS) for pain, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), wound healing, and bone fusion.The meta-analysis showed that preoperative OAT duration of 1 to 2 weeks significantly reduced inflammation, with a notable decrease in ESR and CRP post-surgery (p = 0.006 for ESR, p = 0.02 for CRP). However, no significant differences in functional recovery or wound healing were observed between shorter (1-2 weeks) and longer (2-4 weeks) OAT durations. Bone fusion results were similar across both groups. A shorter duration of OAT preoperatively (1-2 weeks) is effective in reducing inflammation and improving postoperative recovery, though it does not significantly impact bone healing or fusion. Thus, a shorter preoperative OAT regimen can be considered a viable option in managing spinal TB patients.